Bullying: construção da inteligência emocional das crianças como forma de intervenção - Amoedo, Elaila Barbosa (Brasil, 2023)
The study, which flourishes here, aims to bring to light the importance of developing the child's affectivity/emotional intelligence as a strategy to combat the practice of bullying in the classroom. In the meantime, we seek, through the perception of teachers about the problem, to know their knowledge, identification skills and their ways of intervening in cases of violence, and also to propose strategies, based on the BNCC, that help to develop intelligence students' emotions. This work is a qualitative approach, carried out through field research. For this, semi-structured interviews were carried out with nine teachers from two schools of the state public education network in the early years of elementary school, bringing to light, from the perception of teachers, the importance of combating bullying. Through the data collected in the interviews, it is possible to perceive the obstacles to the work of preventing bullying, such as lack of training of teachers on the subject, little or no family education and trivialization of prejudice.